Polyimide paper core tape based on aramid mica coating and preparation method thereof

By using aramid mica coating polyimide paper core wrapping method in the cable core wrapping material, the problem of insufficient temperature resistance and insulation performance of the existing cable core wrapping material is solved, and efficient and environmentally friendly Preparation of cable core strap material.

CN117488577BActive Publication Date: 2025-02-14SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311436906.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-02-14
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing cable core strap materials have low temperature resistance and limited insulation performance due to the use of silicone, and the volatility of silicone solvents poses environmental and human safety threats.

Method used

Using a polyimide paper core-packing tape preparation method based on aramid mica coating, the traditional silicone adhesive and PET are replaced by the composite treatment of polyimide fiber paper, aramid nanofiber gel and hydroxylated mica scales. Baseband realizes self-adhesion and efficient hot press drying of mica.

Benefits of technology

The temperature resistance level and insulation performance of the cable core strap are improved, the volatility of organic solvents is avoided, and the environmental and human safety risks are reduced. The process has the advantages of green, noise-free and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117488577B_ABST
    Figure CN117488577B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of special cable core tape material preparation, and in particular to a polyimide paper core tape based on aramid mica coating and a preparation method thereof, wherein the preparation method comprises the following steps: S1, preparation of polyimide fiber paper and aramid nanofiber gel; step 2: uniformly mixing the aramid nanofiber gel and mica flakes and then scraping and coating them on the surface of the polyimide fiber paper, and drying to obtain the aramid mica scraped cable core tape. The method of scraping and coating the polyimide fiber paper with aramid mica blended gel to form a high-performance cable core tape proposed by the present invention has high feasibility in the actual engineering process, and lays a foundation for mass production of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable auxiliary material preparation, and specifically relates to a polyimide paper core wrapping tape based on aramid mica coating and a preparation method thereof. Background Art

[0002] Mica flakes are highly insulated, corona-resistant, and high-temperature resistant, and are indispensable auxiliary materials for insulation and heat insulation of special cables. However, the interface of mica flakes is highly inert, and they have almost no strength when they are made into paper independently. In order to solve this problem, the traditional cable core wrapping tape manufacturing usually introduces silicone and PET base tape as adhesives, reinforcements, and support materials. However, the temperature resistance of silicone is 115°C and that of PET is 160°C, which is low and easy to age, resulting in the overall insulation, temperature resistance, and service life of the cable core wrapping tape being reduced, and it cannot meet the application requirements of high-end cables in special fields such as nuclear power, high-speed rail locomotives, aerospace, and national defense and military industries. In order to solve this problem, Zhang Yun and others invented (ZL201310114775.7) a composite core wrapping tape material with glass fiber cloth / polyester as the support material. Although it avoids the shortcomings caused by the PET base tape, the solvent used for silicone is toluene, which still causes volatile organic solvent pollution and harms the environment and human safety. This project invented a polyimide fiber paper-based cable core wrapping tape based on aramid mica coating, which solved the above-mentioned problems of temperature resistance and organic solvent volatilization. Summary of the invention

[0003] Aiming at the problem that silica gel limits the temperature resistance grade of cable core tape and causes volatile organic solvents, the present invention provides a polyimide paper core tape based on aramid mica coating and a preparation method thereof.

[0004] The present invention is achieved through the following technical solutions:

[0005] A method for preparing a polyimide paper core tape based on aramid mica coating comprises the following steps:

[0006] S1, preparation of polyimide fiber paper, hydroxylated mica flakes, and aramid nanofiber gel;

[0007] The preparation method of polyimide fiber paper is as follows: firstly, the polyimide fiber is soaked in a soaking system prepared by potassium hydroxide solution / dimethyl sulfoxide solution, then washed with acetic acid and dried to obtain activated polyimide fiber; then, the activated polyimide fiber and aramid fiber are wet-formed by a deflaker and a paper sheet former, and then the polyimide fiber paper is obtained by pressing, dehydrating and drying;

[0008] The preparation method of aramid nanofiber gel is as follows: aramid fiber, potassium hydroxide solution and dimethyl sulfoxide are subjected to chemical cracking and filtration to prepare high-concentration aramid nanofiber gel;

[0009] Hydroxylation treatment of mica flakes: After soaking the phlogopite flakes in a dilute sodium hydroxide solution for hours, washing and drying, hydroxylated mica flakes are obtained;

[0010] S2, mixing the aramid nanofiber gel, the polyvinyl alcohol solution, and the hydroxylated phlogopite flakes uniformly by stirring to obtain an aramid-mica mixture;

[0011] S3, coating the aramid mica mixture on the surface of the polyimide fiber paper by scraping, and preparing the polyimide fiber / aramid mica composite cable core wrapping tape material by hot pressing and drying.

[0012] Preferably, in the preparation process of the polyimide fiber paper of S1, the polyimide fiber is a wholly aromatic polyimide fiber synthesized from pyromellitic anhydride and p-phenylenediamine, the soaking system is prepared by 0.5 g / mL potassium hydroxide solution and dimethyl sulfoxide in a volume ratio of (1-3) mL:300 mL, and the soaking time is 5 to 10 min; the concentration of acetic acid during cleaning is 0.001-0.008 mol / L.

[0013] Preferably, in the preparation process of the polyimide fiber paper of S1, the mass ratio of polyimide fiber to aramid fiber is 6:4, the number of revolutions of fiber decomposition is (15000-20000) revolutions, and the concentration of the mixed slurry is (2.4-2.8) g / L.

[0014] Preferably, in the preparation process of the polyimide fiber paper of S1, when the paper is pressed and dehydrated, the pressing time is 8 to 10 minutes and the pressure is 5 to 9 MPa; when drying, the time is (10-15) minutes and the temperature is (110 to 120)°C.

[0015] Preferably, in the hydroxylation treatment of mica flakes in S1, the concentration of dilute sodium hydroxide is (0.1-0.5) g / L, the cleaning is performed by rinsing with water, and the drying is performed by drying in a vacuum oven at (60-80)°C for (5-6) hours.

[0016] Preferably, in the preparation process of the aramid nanofiber gel of S1, the aramid nanofiber gel is para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide, which are mixed in the ratio of (1-2 g) g: (1-3) mL: (200-400) mL in sequence, and then magnetically stirred for (10-20) h to obtain an aramid nanofiber solution.

[0017] Preferably, in the preparation process of the aramid nanofiber gel of S1, the prepared aramid nanofiber solution is separated, dispersed and filtered by adding water to obtain a high-concentration aramid nanofiber gel with a concentration of (1 to 4) mg / mL.

[0018] Preferably, in S2, the aramid-mica mixture is prepared by uniformly mixing aramid nanofiber gel, polyvinyl alcohol solution, and phlogopite flakes in the ratio of (3-5) g: (1-2) mL: (6-10) g, wherein the concentration of the polyvinyl alcohol solution is (0.2-0.8) mg / mL.

[0019] Preferably, in S2, the coating amount of the aramid-mica mixture is (20-25) g / m 2 ; During hot press drying, the temperature is 100-105°C, the pressure is 5-8MPa, and the time is 10-15min.

[0020] A cable core tape prepared by a method for preparing a polyimide paper core tape based on aramid mica coating.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The method for preparing a polyimide paper core tape based on aramid mica coating of the present invention includes the steps of polyimide fiber interface activation, polyimide fiber papermaking, mica flake hydroxylation, aramid nanofiber gel preparation, aramid mica coating and compounding, and the process has the advantages of being green, noise-free and efficient while ensuring the self-adhesion of mica. Secondly, in view of the problems of low temperature resistance, limited insulation performance, and volatilization of organic solvent toluene caused by the previous preparation of cable core tape materials with silicone adhesive mica paper, the present invention replaces the silicone adhesive and PET base tape with aramid nanofiber gel, uses aramid nanofiber gel to bond mica and scrapes it on the surface of polyimide fiber paper, and produces a high-performance cable core tape composited with paper film, which solves the environmental and safety problems caused by the silicone adhesive of cable core tape on the existing market.

[0023] The polyimide paper core tape based on aramid mica coating and the preparation method thereof propose that mica flakes are blended with aramid nanofibers and polyvinyl alcohol and bonded on the surface of polyimide fiber paper, which gives the present invention higher feasibility in the actual engineering process and lays a foundation for mass production.

[0024] In order to improve the bonding within the paper fiber and the bonding of the aramid cloud coating, the present invention pre-hydrolyzes the polyimide fiber surface with alkali solution to provide attachment sites. The mechanism is that the imide group is hydrolyzed by the alkaline organic environment to form a carboxyl active group.

[0025] Finally, in order to further enhance the bonding force between aramid and mica, the present invention pre-treats the mica flakes with sodium hydroxide solution to promote the formation of hydroxyl groups on the mica flakes, which form extensive hydrogen bonds with the amide groups on the surface of the aramid nanofibers when dried. In order to increase the contact area for hydrogen bond formation, the present invention preferably introduces hydroxyl-rich polyvinyl alcohol as a supplement, thereby completely avoiding the use of silica gel in traditional processes.

[0026] In addition, the reagents used in the preparation of the present invention are all conventional pharmaceutical reagents, which are low-toxic, cheap and easy to obtain, and the equipment used are all conventional instruments and equipment, which lays a foundation for the commercialization of the process technology products protected by the invention, reduces costs and improves market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the method for preparing the polyimide paper core tape based on aramid mica coating of the present invention;

[0028] Figure 2 SEM image of the surface of the polyimide fiber paper cable core tape based on aramid mica coating in Example 1 of the present invention.

[0029] Figure 3 This is a surface SEM image of the polyimide fiber paper cable core tape based on aramid mica coating in Example 3 of the present invention.

[0030] Figure 4 This is a cross-sectional SEM image of the polyimide fiber paper cable core tape based on aramid mica coating in Example 5 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0032] The present invention discloses a method for preparing a polyimide paper core tape based on aramid mica coating, referring to Figure 1 , including the following steps:

[0033] S1, Preparation of polyimide fiber paper, hydroxylated mica flakes, and aramid nanofiber gel.

[0034] The preparation method of polyimide fiber paper is as follows: first, the polyimide fiber (wholly aromatic polyimide fiber synthesized from pyromellitic anhydride and p-phenylenediamine) is soaked in a soaking system prepared from potassium hydroxide solution / dimethyl sulfoxide solution (prepared from 0.5 g / mL potassium hydroxide solution and dimethyl sulfoxide according to a volume ratio of (1-3) mL: 300 mL) for 5 to 10 minutes, and then washed with acetic acid with a concentration of 0.001-0.008 mol / L (for neutralizing the alkali remaining on the surface) and dried to obtain activated polyimide fiber. Then, the activated polyimide fiber and aramid fiber are wet-formed by a deflaking machine and a paper sheet former at a mass ratio of 6:4, and then the polyimide fiber paper is obtained by pressing, dehydrating and drying.

[0035] The number of revolutions of the deflaker during deflaking is 15,000 to 20,000 revolutions, and the concentration of the mixed slurry is 2.4 to 2.8 g / L. During wet forming in the paper former, the paper is pressed and dehydrated for 8 to 10 minutes at a pressure of 5 to 9 MPa; during drying, the time is 10 to 15 minutes at a temperature of 110 to 120°C.

[0036] The preparation method of aramid nanofiber gel is as follows: aramid fiber, potassium hydroxide solution and dimethyl sulfoxide are subjected to chemical cracking and filtration to prepare a high-concentration aramid nanofiber gel; specifically, para-aramid fiber, potassium hydroxide solution and dimethyl sulfoxide are sequentially mixed in a ratio of (1-2 g) g: (1-3) mL: (200-400) mL, and then magnetically stirred for (10-20) h to obtain an aramid nanofiber solution. The prepared aramid nanofiber solution is then separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of (1-4) mg / mL.

[0037] Hydroxylation treatment of mica flakes: immerse the phlogopite flakes in a dilute sodium hydroxide solution, wash and dry to obtain hydroxylated mica flakes; the concentration of the dilute sodium hydroxide is (0.1-0.5) g / L, washing is performed by rinsing with tap water, and drying is performed by drying in a vacuum oven at (60-80)°C for (5-6) hours.

[0038] S2, mixing the aramid nanofiber gel, a polyvinyl alcohol solution with a concentration of (0.2-0.8) mg / mL, and hydroxylated phlogopite flakes in a ratio of (3-5) g: (1-2) mL: (6-10) g to obtain an aramid mica mixture;

[0039] SS, apply the aramid-mica mixture at a scraping amount of (20-25) g / m 2 The polyimide fiber / aramid mica composite cable core tape material is obtained by coating it on the surface of polyimide fiber paper and drying it by hot pressing (temperature of 100-105° C., pressure of 5-8 MPa, time of 10-15 min).

[0040] The invention also discloses a polyimide paper core wrap tape prepared by a method for preparing a polyimide paper core wrap tape based on aramid mica coating.

[0041] Example 1

[0042] Step 1, preparing a potassium hydroxide solution / dimethyl sulfoxide system according to a volume ratio of 1 mL:300 mL of potassium hydroxide solution and soaking the polyimide fiber in the potassium hydroxide solution / dimethyl sulfoxide system for 5 minutes to achieve micro-etching, then washing with acetic acid and drying for standby use, wherein the concentration of the potassium hydroxide solution is 0.5 g / mL and the concentration of the acetic acid is 0.005 mol / L;

[0043] Step 2, the polyimide fiber and aramid fiber precipitated after micro-etching in the previous step are slurried in a mass ratio of 6:4 to form a mixed slurry with a concentration of 2.4 g / L, and the slurry is deflaked by a deflaker at 15,000 revolutions, and then dehydrated by a paper former, pressed by a press at 8 MPa for 10 min, and dried at 110° C. for 10 min to prepare polyimide fiber paper;

[0044] Step 3, soak the phlogopite mica flakes in a dilute sodium hydroxide solution with a concentration of 0.1 g / L for 5 hours, wash them twice with tap water, and dry them in a vacuum oven at 60° C. for 5 hours;

[0045] Step 4: para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide are sequentially mixed in a ratio of 1 g: 1 mL: 200 mL, and magnetically stirred for 15 h to obtain an aramid nanofiber solution; the prepared aramid nanofiber solution is separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of 1 mg / mL;

[0046] Step 5: The aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes are mixed uniformly according to 3 g: 1 mL: 6 g to obtain the aramid mica gel, wherein the concentration of the polyvinyl alcohol solution is 0.2 mg / mL;

[0047] Step 6: According to 20g / m 2 The aramid mica gel was scraped onto the surface of the polyimide fiber paper, and the polyimide fiber / aramid mica composite cable core tape was prepared by hot pressing and drying at 8 MPa and 105°C for 10 min.

[0048] The cable core tape prepared in Example 1 is as follows Figure 2 As shown, its dielectric strength is 43.5kv / mm, limiting oxygen index is 44%, tensile strength is 63.2N / cm, and volume resistivity is 9.1×10 13 Ω·m, temperature resistance grade C (above 180℃). Figure 1 It can be seen that the surface of the polyimide fiber is densified by the aramid mica and the surface is very smooth without leaving any pores in the paper, which indicates that the coating of the aramid mica gel has greatly improved the surface of the paper.

[0049] Example 2

[0050] Step 1, preparing a potassium hydroxide solution / dimethyl sulfoxide system according to a volume ratio of 2 mL:300 mL of potassium hydroxide solution and soaking the polyimide fiber in the potassium hydroxide solution / dimethyl sulfoxide system for 6 minutes to achieve micro-etching, then washing with acetic acid and drying for standby use, wherein the concentration of the potassium hydroxide solution is 0.5 g / mL and the concentration of the acetic acid is 0.005 mol / L;

[0051] Step 2, the polyimide fiber and aramid fiber precipitated after micro-etching in the previous step are slurried in a mass ratio of 6:4 to form a mixed slurry with a concentration of 2.5 g / L, and the slurry is deflaked by a deflaker at 17,000 revolutions, and then dehydrated by a paper sheet former, pressed by a press at 8 MPa for 10 min, and dried at 110° C. for 11 min to prepare polyimide fiber paper;

[0052] Step 3, soaking the phlogopite mica flakes in a dilute sodium hydroxide solution with a concentration of 0.3 g / L for 6 hours, washing them twice with tap water, and drying them in a vacuum oven at 70° C. for 5.5 hours;

[0053] Step 4: para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide were mixed in a ratio of 1.5 g: 2 mL: 300 mL, and magnetically stirred for 17 h to obtain an aramid nanofiber solution; the prepared aramid nanofiber solution was separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of 2 mg / mL;

[0054] Step 5: The aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes are mixed evenly according to 4 g: 1 mL: 7 g to obtain the aramid mica gel, wherein the concentration of the polyvinyl alcohol solution is 0.3 mg / mL;

[0055] Step 6: According to 21g / m 2 The aramid mica gel was scraped onto the surface of the polyimide fiber paper, and the polyimide fiber / aramid mica composite cable core tape was prepared by hot pressing and drying at 8 MPa and 105°C for 10 min.

[0056] The cable core tape prepared in Example 2 has a dielectric strength of 42.1 kV / mm, a limiting oxygen index of 46%, a tensile strength of 61.4 N / cm, and a volume resistivity of 8.9×10 14 Ω·m, temperature resistance grade C (above 180℃).

[0057] Example 3

[0058] Step 1, preparing a potassium hydroxide solution / dimethyl sulfoxide system according to a volume ratio of 3 mL:300 mL of potassium hydroxide solution and soaking the polyimide fiber in the potassium hydroxide solution / dimethyl sulfoxide system for 8 minutes to achieve micro-etching, then washing with acetic acid and drying for standby use, wherein the concentration of the potassium hydroxide solution is 0.5 g / mL and the concentration of the acetic acid is 0.005 mol / L;

[0059] Step 2, the polyimide fiber and aramid fiber precipitated after micro-etching in the previous step are slurried in a mass ratio of 6:4 to form a mixed slurry with a concentration of 2.6 g / L, and the slurry is deflaked by a deflaker at 18,000 revolutions, and then dehydrated by a paper former, pressed by a press at 8 MPa for 10 min, and dried at 115° C. for 13 min to prepare polyimide fiber paper;

[0060] Step 3, soak the phlogopite mica flakes in a dilute sodium hydroxide solution with a concentration of 0.3 g / L for 7 hours, wash them twice with tap water, and dry them in a vacuum oven at 70° C. for 5.7 hours;

[0061] Step 4: Para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide were mixed in a ratio of 1.6 g: 2.5 mL: 350 mL, and magnetically stirred for 17 h to obtain an aramid nanofiber solution; the prepared aramid nanofiber solution was separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of 3 mg / mL;

[0062] Step 5: The aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes are mixed uniformly according to 4 g: 1.8 mL: 8 g to obtain the aramid mica gel, wherein the concentration of the polyvinyl alcohol solution is 0.6 mg / mL;

[0063] Step 6: According to 24g / m 2 The aramid mica gel was scraped onto the surface of the polyimide fiber paper, and the polyimide fiber / aramid mica composite cable core tape was prepared by hot pressing and drying at 8 MPa and 105°C for 10 min.

[0064] The cable core tape prepared in Example 3 is as follows Figure 3 As shown, its dielectric strength is 41.0kv / mm, limiting oxygen index is 49%, tensile strength is 74.5N / cm, and volume resistivity is 8.7×10 15 Ω·m, temperature resistance grade C (above 180℃). Figure 2 It can be seen that the polyimide fibers and mica flakes are tightly wrapped by the aramid nanofibers, and no paper is left, which shows that the scraping of aramid mica gel has improved the surface smoothness of the paper well, and also explains the source of the strength of the cable core tape.

[0065] Example 4

[0066] Step 1, preparing a potassium hydroxide solution / dimethyl sulfoxide system according to a volume ratio of 3 mL:300 mL of potassium hydroxide solution and soaking the polyimide fiber in the potassium hydroxide solution / dimethyl sulfoxide system for 10 minutes to achieve micro-etching, then washing with acetic acid and drying for standby use, wherein the concentration of the potassium hydroxide solution is 0.5 g / mL and the concentration of the acetic acid is 0.005 mol / L;

[0067] Step 2, the polyimide fiber and aramid fiber precipitated after micro-etching in the previous step are slurried in a mass ratio of 6:4 to form a mixed slurry with a concentration of 2.8 g / L, and the slurry is deflaked by a deflaker at 20,000 revolutions, and then dehydrated by a paper former, pressed by a press at 8 MPa for 10 minutes, and dried at 120° C. for 15 minutes to prepare polyimide fiber paper;

[0068] Step 3, soaking the phlogopite mica flakes in a dilute sodium hydroxide solution with a concentration of 0.5 g / L for 8 hours, washing them twice with tap water, and drying them in a vacuum oven at 80° C. for 6 hours;

[0069] Step 4: para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide are sequentially mixed in a ratio of 2 g: 3 mL: 400 mL, and magnetically stirred for 20 h to obtain an aramid nanofiber solution; the prepared aramid nanofiber solution is separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of 4 mg / mL;

[0070] Step 5: The aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes are mixed evenly according to 5 g: 2 mL: 10 g to obtain the aramid mica gel, wherein the concentration of the polyvinyl alcohol solution is 0.8 mg / mL;

[0071] Step 6: According to 25g / m 2 The aramid mica gel was scraped onto the surface of the polyimide fiber paper, and the polyimide fiber / aramid mica composite cable core tape was prepared by hot pressing and drying at 8 MPa and 105°C for 10 min.

[0072] The cable core tape prepared in Example 3 has a dielectric strength of 45.4 kV / mm, a limiting oxygen index of 46%, a tensile strength of 72.6 N / cm, and a volume resistivity of 8.5×10 14 Ω·m, temperature resistance grade C.

[0073] Example 5

[0074] Step 1, preparing a potassium hydroxide solution / dimethyl sulfoxide system according to a volume ratio of 3 mL:300 mL of potassium hydroxide solution and soaking the polyimide fiber in the potassium hydroxide solution / dimethyl sulfoxide system for 10 minutes to achieve micro-etching, then washing with acetic acid and drying for standby use, wherein the concentration of the potassium hydroxide solution is 0.5 g / mL and the concentration of the acetic acid is 0.005 mol / L;

[0075] Step 2, the polyimide fiber and aramid fiber precipitated after micro-etching in the previous step are slurried in a mass ratio of 6:4 to form a mixed slurry with a concentration of 2.7 g / L, and the mixed slurry is deflaked by a deflaker at 19,000 revolutions, and then dehydrated by a paper sheet former, pressed by a press at 8 MPa for 10 minutes, and dried at 118° C. for 13 minutes to prepare polyimide fiber paper;

[0076] Step 3, soaking the phlogopite mica flakes in a dilute sodium hydroxide solution with a concentration of 0.4 g / L for 7 hours, washing them twice with tap water, and drying them in a vacuum oven at 70° C. for 6 hours;

[0077] Step 4: para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide are sequentially mixed in a ratio of 2 g: 1 mL: 200 mL, and magnetically stirred for 16 h to obtain an aramid nanofiber solution; the prepared aramid nanofiber solution is separated by adding water, decomposed and filtered to obtain a high-concentration aramid nanofiber gel with a concentration of 2 mg / mL;

[0078] Step 5: The aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes are mixed evenly according to 4 g: 1 mL: 6 g to obtain the aramid mica gel, wherein the concentration of the polyvinyl alcohol solution is 0.7 mg / mL;

[0079] Step 6: According to 22g / m 2 The aramid mica gel was scraped onto the surface of the polyimide fiber paper, and the polyimide fiber / aramid mica composite cable core tape was prepared by hot pressing and drying at 8 MPa and 105°C for 10 min.

[0080] The cable core tape prepared in Example 5 is as follows Figure 4 As shown, its dielectric strength is 42.7kv / mm, limiting oxygen index is 42%, tensile strength is 76.3N / cm, and volume resistivity is 8.7×10 14 Ω·m, temperature resistance grade C. Figure 4 It can be seen that the surface of the polyimide fiber paper is tightly wrapped by the aramid mica layer, and it is a thin layer, which means that after the aramid mica gel is applied and dried, a good structure of paper below and film above is formed. This indirectly reflects the functions of the aramid mica layer, one is to assist in improving strength, and the other is to avoid the air breakdown effect caused by the pores of the paper.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a polyimide paper core tape based on aramid mica coating, characterized in that: The steps include: S1, preparation of polyimide fiber paper, hydroxylated mica flakes, and aramid nanofiber gel; The preparation method of the polyimide fiber paper is as follows: firstly, the polyimide fiber is soaked in a soaking system prepared by potassium hydroxide solution / dimethyl sulfoxide solution, and activated polyimide fiber is obtained after washing and drying; then, the activated polyimide fiber and aramid fiber are formed by wet method to obtain polyimide fiber paper; The preparation method of aramid nanofiber gel is as follows: aramid fiber, potassium hydroxide solution and dimethyl sulfoxide are subjected to chemical cracking and filtration to prepare high-concentration aramid nanofiber gel; Hydroxylation treatment of mica flakes: soaking the phlogopite flakes in a dilute sodium hydroxide solution, washing and drying to obtain hydroxylated mica flakes; S2, mixing the aramid nanofiber gel, the polyvinyl alcohol solution, and the hydroxylated phlogopite flakes by stirring to obtain an aramid mica mixture; wherein the aramid mica mixture is obtained by mixing the aramid nanofiber gel, the polyvinyl alcohol solution, and the phlogopite flakes in the ratio of (3-5) g: (1-2) mL: (6-10) g, wherein the concentration of the polyvinyl alcohol solution is (0.2-0.8) mg / mL; S3, coating the aramid mica mixture on the surface of the polyimide fiber paper by scraping, and preparing the polyimide fiber / aramid mica composite cable core wrapping tape material by hot pressing and drying.

2. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In the preparation process of the polyimide fiber paper of S1, the polyimide fiber is a wholly aromatic polyimide fiber synthesized from pyromellitic anhydride and p-phenylenediamine, the soaking system is prepared by 0.5 g / mL potassium hydroxide solution and dimethyl sulfoxide in a volume ratio of (1-3) mL: 300 mL, and the soaking time is 5 to 10 min; the concentration of acetic acid during cleaning is 0.001-0.008 mol / L.

3. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In the preparation process of the polyimide fiber paper of S1, the mass ratio of polyimide fiber to aramid fiber is 6:4, the number of revolutions of fiber decomposition is (15000-20000) revolutions, and the concentration of the mixed slurry is (2.4-2.8) g / L.

4. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In the preparation process of S1 polyimide fiber paper, when the paper is pressed and dehydrated, the pressing time is 8~10 min and the pressure is 5~9MPa; when drying, the time is (10-15) min and the temperature is (110~120)℃.

5. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In the hydroxylation treatment of mica flakes of S1, the concentration of dilute sodium hydroxide was (0.1-0.5) g / L, the cleaning was performed by rinsing with tap water, and the drying was performed by drying in a vacuum oven at (60-80) °C for (5-6) h.

6. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In the preparation process of the aramid nanofiber gel of S1, the aramid nanofiber gel is prepared by mixing para-aramid fiber, potassium hydroxide solution, and dimethyl sulfoxide in a ratio of (1-2) g: (1-3) mL: (200-400) mL, followed by magnetic stirring for (10-20) h to obtain an aramid nanofiber solution.

7. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 6, characterized in that: In the preparation process of the aramid nanofiber gel of S1, the prepared aramid nanofiber solution is separated, dispersed, and filtered by adding water to obtain a high-concentration aramid nanofiber gel with a concentration of (1 to 4) mg / mL.

8. The method for preparing a polyimide paper core tape based on aramid mica coating according to claim 1, characterized in that: In S2, the coating amount of aramid-mica mixture is (20-25) g / m 2 ; During hot press drying, the temperature is 100~105℃, the pressure is 5~8MPa, and the time is 10~15min.

9. A cable core tape prepared by the method for preparing a polyimide paper core tape based on aramid mica coating according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite mica tape and manufacturing process thereof

    CN103268796A

  • Para-aramid pulp enhanced polyimide fiber paper preparation method

    CN102953288A

  • Aramid nanofiber reinforced cable core belting material and preparation method thereof

    CN115923210A